Law Dome Ice Core 2000-Year CO2, CH4, N2O and d13C-CO2 ... - Rubino, Mauro; Etheridge, David; Thornton, David; Allison, Colin; Francey, Roger; Langenfelds, Ray; Steele, Paul; Trudinger, Cathy; Spencer, Darren; Curran, Mark; Van Ommen, Tas; Smith, Andrew (CSIRO, 2019)
Law Dome ice core (DSS, DSS0506, DE08 and DE08-2) and firn air (DE08-2 and DSSW20K) records of CO2, CH4 and N2O concentrations for the past 2000 years and d13C-CO2 for the past 1000 years. Law Dome location: The dome summit is as follows, individual cores are within about 25 km (see publications), 66°44'S, 112°50'E, 1390m elevation. ...